Investigation on possibility of mechanochemical synthesis of CaTiO3 from different precursors - Brankovic, G.; Vukotic, V.; Brankovic, Z.; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Recently, mechanochemical synthesis was widely used in preparation of perovskite type of materials, such as BaTiO3, PbTiO3, PZT, etc. In this work, the possibility of mechanochemical synthesis of CaTiO3 from different precursors, such as CaCO3 or CaO and TiO2 was investigated. Intensive milling of mixture of CaO and TiO2, under optimal milling conditions, resulted in synthesis of single phase CaTiO3. It was also found that intensive milling of powder mixture containing CaCO3 and TiO2 only activate the powders for the sintering process; hence the CaTiO3 could be obtained at lower temperatures of sintering. To complete reaction of CaTiO3 formation during milling it is necessary to reduce CO2 partial pressure, i.e. it is necessary to change the atmosphere inside the vials during milling. In this work, an explanation for difference in milling behavior of different precursors was proposed and discussed. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: milling; powders-solid state reaction; perovskites; x-ray method